Pathological mechanisms and future therapeutic directions of thrombin in intracerebral hemorrhage: a systematic review - Chenxi Tao; Chenxi Tao; Yuanyuan Li; Yuanyuan Li; Na An; Haoqi Liu; Zhenhong Liu; Zhenhong Liu; Yikun Sun; Ying Qian; Na Li; Yanwei Xing; et al. (Frontiers Media S.A., 2024)
Intracerebral hemorrhage (ICH), a common subtype of hemorrhagic stroke, often causes severe disability or death. ICH induces adverse events that might lead to secondary brain injury (SBI), and there is currently a lack of specific effective treatment strategies. To provide a new direction for SBI treatment post-ICH, the systematic review discussed how thrombin impacts secondary injury after ICH through several potentially deleterious or protective mechanisms. We included 39 studies and evaluated them using SYRCLE's ROB tool. Subsequently, we explored the potential molecular mechanisms of thrombin-mediated effects on SBI post-ICH in terms of inflammation, iron deposition, autophagy, and angiogenesis. Furthermore, we described the effects of thrombin in endothelial cells, astrocytes, pericytes, microglia, and neurons, as well as the harmful and beneficial effects of high and low thrombin concentrations on ICH. Finally, we concluded the current research status of thrombin therapy for ICH, which will provide a basis for the future clinical application of thrombin in the treatment of ICH.